Proceso de ASC - ESTUDIO DE MATERIALES CON MEMORIA DE FORMA EN LA CONSTRUCCION DE MUSCULOS ARTIFICIALES (2021)
Materials have different properties that distinguish them from one another, some of which are used to our advantage in the development of new technologies that enable day-to-day advancements. In this project, the properties of certain materials were studied to allow the design and construction of artificial muscles. These materials are those that exhibit the SME (Shape Memory Effect), particularly shape memory polymers. Throughout the project, relevant research was conducted on the existing theory, the fundamental physical and chemical phenomena of the problem, and the creation of shape memory polymers that enable the development of artificial muscles.